Ionizing radiation induces cutaneous lipid remolding and skin adipocytes confer protection against radiation-induced skin injury. Issue 2 (February 2020) - Xiao, Yuji; Mo, Wei; Jia, Huimin; Yu, Daojiang; Qiu, Yuyou; Jiao, Yang; Zhu, Wei; Koide, Hiroshi; Cao, Jianping; Zhang, Shuyu
Highlights: Radiation modulates the expression of lipid metabolism-related genes and decreases skin fat mass with altered lipid metabolite profiles. Increased skin adipose mass induced by a high-fat diet confers resistance against radiogenic skin injury. Fatty acid binding protein 4 (FABP4) from skin adipocytes could be incorporated into skin cells and promote DNA damage repair. Abstract: Background: Radiation-induced skin injury is a serious concern during radiotherapy and radiation accidents. Skin fat represents the dominant architectural component of the human skin. However, the interplay between skin fat and the progression of radiation-induced skin injury remains largely unexplored. Objective: This study aims to elucidate the interplay between skin fat and the progression of radiation-induced skin injury. Methods: SD rats were irradiated with an electron beam. mRNA profiles were determined by RNA-Seq. The skin lipid mass was monitored by magnetic resonance imaging (MRI) and lipid profiles were measured by liquid chromatography-mass spectrometry (LC–MS). Human mature adipocytes isolated from dermal and subcutaneous white adipose tissues (WATs) were co-cultured with human keratinocytes (HaCaT) and skin fibroblasts (WS1) in the transwell culture system. Cell migration ability was measured by migration assay. Results: Radiation modulated cutaneous lipid metabolism by downregulating multiple pathways. Moreover, radiation decreased skin fat mass with altered lipid metabolite profiles. The rats fed with a high-fat diet showed resistance to radiogenic skin injury compared with that with a control diet, indicating that skin lipid plays a radioprotective role. Mature adipocytes promoted the migration but not the proliferation of co-cultured skin keratinocytes and fibroblasts. Palmitic acid, the most abundant fatty acid in skin tissues, facilitated the migration of WS1 cells. Moreover, fatty acid-binding protein 4 (FABP4) could be incorporated into skin cells and promote DNA damage repair in irradiated skin fibroblasts. Conclusion: Radiation induces cutaneous lipid remolding, and skin adipocytes confer a protective role against radiation-induced skin injury.